profile
Опубликовано - 2 месяца назад | По предмету Математика | автор Аноним

(x^2-8x+7)*(x^2-8x+15)=-15

  1. Ответ
    Ответ дан Лихачёва Дарья

    (x ^ 2 - 8 * x + 7) * (x ^ 2 - 8 * x + 15) = - 15; 

    n

    Пусть x ^ 2 - 8 * x = a, тогда получим: 

    n

    (a + 7) * (a + 15) = - 15; 

    n

    a * a + 15 * a + 7 * a + 7 * 15 = - 15; 

    n

    a ^ 2 + 15 * a + 7 * a + 7 * 15 + 15 = 0; 

    n

    a ^ 2 + 22 * a + 15 * (7 + 1) = 0; 

    n

    a ^ 2 + 22 * a + 15 * 8 = 0; 

    n

    a ^ 2 + 22 * a + 120 = 0; 

    n

    D = b2 - 4ac = 222 - 4·1·120 = 484 - 480 = 4; 

    n

    a1 = (- 22 - √4)/(2 * 1) = (- 22 - 2)/2 = - 24/2 = - 12;  

    n

    a2 = (- 22 + √4)/(2 * 1) = (- 22 + 2)/2 = - 20/2 = - 10;   

    n

    Тогда: 

    n

    { x ^ 2 - 8 * x = - 12; 

    n

    x ^ 2 - 8 * x = - 10; 

    n

    { x ^ 2 - 8 * x + 12 = 0; 

    n

    x ^ 2 - 8 * x + 10 = 0; 

    n

    { x1 = 2 и x2 = 6; 

    n

    x3 = 4 - √6 и x4 = 4 + √6. 

    0



Топ пользователи